(3GdeDKQGJ heaJGM GdeTcdGJs - (3CHh eMeO GdMSf Hf eMeO Hf GdMSf Hf eMeO GdQUGU,J (B584 (3g` s ((3YR GdOjf Hf GdMSf Hf CejQ GdeDefjf s)
(3ChdgG (B:s
(3GdMeO ddg NGdb GdCQVjf hGdSeGhGJ GdPi Edjg JfJgi GdJCKjQGJ hGdeDKQGJ SGdJ (B_ (3habfG Gddg hCjGc (B_ (3Cf ChVM dc LedI ai GdeDKQGJ heG jLi eLQGgG ef GdTQhW s
(3BNQgG (B:s
(3hbO HjfG GdcdGe ai Pdc Ydi WQjbI GdELeGd Ohf GdJaVjd , hGddg hdi GdJhajb Je s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI eUMMIs
(3Ydi ZGTjJgG eG jajO ebGHdJgG hHJUMjMgG hbQGAJgG s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
Keywords: (3GdJhMjO hGdedd hGdfMds